Elemente einer Soziolinguistik Nordafrikas - Wolff, H Ekkehard (Stellenbosch Papers in Linguistics Plus, 2012)
The sociolinguistics of the Northern African states is relatively obscure in terms of international research, since these regions do not feature significantly in the areas of Arabic studies/Orientalism, Romance studies or classical African studies. A similar problem holds for the scientific classification of studies on Berber. This article develops an africanist-sociolinguistic approach to central questions refering to multilingualism in the context of historically unfolding geo- and sociolinguistic profiles of Northern African nations. This will be discussed within the framework of a historical linguistic stratigraphy. The article broadens the concept of diglossia as used in the arabophonic context in order to include a multilingual dimension (polyglotism), and discusses models of conflict avoidance between native speakers of Arabic, Berber and French, respectively. The article focuses on situationally adequate language political arrangements, especially in the area of education, on the basis of L1-based additive bi- and trilingualism models. Keywords: Schlüsselbegriffe : Afrikanistik, Arabisch, Berber, Bildung, Diglossie, Französisch, Maghreb, Mehrsprachigkeit, Polyglossie, Soziolinguistik, Sprachenpolitik African studies, Arabic, Berber, education, diglossia, French, Maghreb, multilingualism, polyglotism, sociolinguistics, language policy